Reliability of rail transit traction drive system-A review. (September 2018) - Lin, Shuai; Fang, Xiaochun; Lin, Fei; Yang, Zhongping; Wang, Xiaofan
Abstract: Traction drive system is an important part of rail transit vehicles, which directly determines whether the train can transport passengers safely, quickly and efficiently. For safety-critical and mission-critical applications, the reliability of traction drive system is still a concern. Study on the reliability of the traction drive system has important guiding significance for the safe operation, after-sale maintenance and components replacement of rail transit. This paper reviews past developments and recent advance in the area of traction drive system reliability evaluation and presents challenges and future research directions in this area. Highlights: Traction drive system is an important part of rail transit vehicles, which directly determines whether the train can transport passengers safely, quickly and efficiently. Study on the reliability of the traction drive system has important guiding significance for the safe operation, after-sale maintenance and components replacement of rail transit. This paper reviews past developments and recent advance in the area of traction drive system reliability evaluation and presents challenges and future research directions in this area. The review has important guiding significance for the concept, design, validation, production, operation, maintenance of rail transit.